Representation of Nature of Science (NoS) in Indonesian Physics Textbooks: a case of heat and temperature concepts - Rahmah Salamah Nur Azizah (Institut Pendidikan Indonesia Garut, 2022)
Learning science including physics cannot be separated from the nature of science or Nature of Sciencen (NoS). Understanding of NoS is very important in the world of education in schools because by understanding NoS students will find it easier to understand the concept of physics in learning at school. For this reason, this study aims to determine the representation of NoS in eleventh grade high school physics textbooks for the concepts of temperature and heat using the content analysis method. The research sample was taken using a purposive sampling technique. Of all the physics textbooks for eleventh grade of high school, only 5 physics textbooks with different publishers analyzed 10 aspects of NoS. The results showed that the frequency of the appearance of the ten aspects of NoS in the five physics textbooks for eleventh grade was different. Book 1 (Erlangga) has 36.64 percent, book 2 (Mediatama) has 18.32 percent, book 3 (Grafindo Media Pratama) and book 4 (Yrama Widya) has the same percentage, namely 14.50 percent. Meanwhile, book 5 (Yudhistira) has an appearance frequency of 16.03 percent. The number of NoS aspects of the five books mostly raises aspects of social and cultural cultivation in science. On the other hand, the aspect that is not raised at all in the five textbooks above is the creative aspect. In general, the five physics textbooks that were analyzed had explicit aspects of NoS, but some were conveyed implicitly. Based on the results of this study it can be concluded that the five physics textbooks have not conveyed aspects of NoS explicitly, correctly and completely.